Investigation of pressure drop in hydro-pneumatic driveline propulsion system for dual hybrid passenger vehicle - F., Wasbari; R. A., Bakar; Gan, L. M.; M. A., Salim; N. A., Hamid; Herawan, S. G. (Penerbit UNIMAP, 2021)
The study focused on investigating the pressure drop/loss of the hydro-pneumatic driveline propulsion system. Previous research has shown that there is a very high power loss in the hydro-pneumatic propulsion system. Therefore, this research is carried out to identify the behaviour, cause and strategy to overcome this problem. The Hydraulic Hybrid Vehicle (HHV) is a new technology under development to improve fuel efficiency in passenger vehicles. However, this system is still under research and development phase. There is still a great deal of uncertainty about the performance of this system. In this research, the functional schematic diagram of the charging and propulsion was designed and simulated by using Automation Studio software. The real-time data and pressure behaviour of hydropneumatic driveline propulsion obtained by running the system without load condition. As a result, the highest value of losses occurred at (psys-p1), stage 1, from the supply to the input of the valve. The value is around 68 to 69 bar and occurred at psys = 220 bar. (p2-p3) showed the lowest losses overall. The lowest pressure loss value occurred at psys = 100 bar, which is around 17 to 18 bar. The pressure drop happened to be high due to the improper selection of hose diameter represented by (psys-p1). The loss of (p1-p2) was due to diameter and angle of connector too sharp that caused disturbance to the flow and p3 is developing back pressure at return line. The stage pressure monitoring was used to narrow down the root cause, and some papers have been used to validate the behaviour.